A Study on the Application of Artificial Intelligence in Chinese Language Teaching in Indonesia - Hu Yaqing; Huang Shanshan; Huang Yuhui; Zheng Haijing; Yennita Oktavia (Proceeding of International Conference on Education, Language, Literacies, and Literary Studies (ICONELS), 2026)
With the acceleration of global digital transformation, Artificial Intelligence (AI) is profoundly reshaping the landscape of International Chinese Language Education. As a key country along the Belt and Road Initiative, Indonesia has witnessed a rapid increase in the demand for Chinese language learning. However, the country continues to face significant shortages of qualified teachers and teaching resources. Taking Indonesia as the research subject, this paper analyzes the current state and major challenges of Chinese language teaching and explores the application of AI technologies in pronunciation correction, Chinese character learning, and personalized instruction. The study aims to provide digital solutions for improving the quality of Chinese language education in Indonesia.